Approaches to Educational Activities and Construction of an Informatics Curriculum - Etinger, Darko; Diković, Marina; Alilović, Hrvoje (Revija za elementarno izobraževanje, 2024)
The research section of the paper explores elementary school students’ satisfaction with informatics. This research was carried out using the American Customer Satisfaction Index (ACSI). Four subscales were used: Expectation, Satisfaction, Quality, and Values. The number of Croatian elementary school pupils investigated (from Brod-Posavina County) is 135 (N). Research results show that pupils have high expectations of informatics, including that it will progressively meet their expectations and help them to receive a quality education. It can also be concluded that the problems once faced by students, such as classroom and equipment quality, are becoming much smaller compared to previous years.
Keywords: American Customer Satisfaction Index (ACSI), computer science curriculum, ICT, informatics, student satisfaction.